ISOLATION AND CHARACTERIZATION OF REACTIVE BLACK DYE DECOLORIZING BACTERIA FROM TEXTILE INDUSTRY - Dhara M. Dobariya (Vidhyayana - An International Multidisciplinary Peer-Reviewed E-Journal - ISSN 2454-8596, 2020)
Textile dye industry waste is one of the most serious problems in the environment. The dye house waste water is severely deleterious to surface water bodies. The present stud was an attempt for the assessment of different physico-chemical parameters such as pH, temperature, Total Solids (TS), Total Suspended solids (TSS), Dissolve Oxygen (DO), Biological Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Total alkalinity, Total hardness and Chloride content of this effluent. Degradation of textile dye is a challenging task for microorganisms as the effluents contain complete chemical, highly toxic compounds and heavy metal. In the present research dye decolorizing bacterial species have been isolated on solid and liquid media. The optimum growth and decolorizing parameters, biochemical characterization and degradation are studies. Identification of the isolates organism based on biochemical test VITEK 2 system, identify mostly Enterobacter species.